Genetic evaluation of rs36513 SNP of UIMC1 and Biochemical Parameters in Early Menopause in Babylon City, Iraq - Rana A. M. Shaker1 , Maha F. Mohammed2 , Bushra j. Al-Rubaey3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Premature menopause or Early menopause (POF) is a condition charecterised by amenorrhea,hypoesteronigism, and elevated serum gonadotrophin level in women younger than 40 years old. This workaimed to evaluate the association of candidate genetic polymorphism in called trans membrane protein 150B (TMEM150B ) and ubiquitin interaction motif containing 1 (UIMC1) also the hormonal changes withPOF in one district of Iraq (province of Babylon) by enrolling Arab ancestors. The genetic variants thatwould be studied in this project were carefully selected according to the recent findings in this field, and byemployed several specialized databases . The selected variant are transmembrane protein 150B (TMEM150B) and ubiquitin interaction motif containing 1 (UIMC1) and their relation with premature ovarian failure.This study include (200) females , their ages between (35-40 years) and body mass index in normal andoverweight, (50) of them were with amenorrhea for 6 months, and the other (150) apparently healthy ascontrol group. Concerning rs365132, the genetic association with POF showed that there was no significantallelic or genotypic association recorded (P > 0.2 ) , except that the patients group was significantly deviatedfrom Hardy-Weinberg equilibrium exact test (P=0.023). For rs11668344, the genetic association with POFshowed that there was no significant allelic or genotypic association recorded (P > 0.2 ) , except that thepatients group was significantly deviated from Hardy-Weinberg equilibrium exact test (P=0.023). Thehormonal results of the present study showed significant increase in FSH in patients compared with controlsgroup. (P < 0.0001) and this study showed significant decrease (p? 0.001) in EST in patients compared withcontrols group. As a conclusion , the study conclude that rs365132 and rs11668344 genes variants do notrepresent genetic factors which can modulate the development of POF in Arab population from Babylonprovince .